Carlson's Trophic State Index for the Assessment of Trophic state of Phewa, Begnas and Rupa Lakes in Kaski district, Nepal - Shrestha, Shristi; Malla, Rabin (Journal of Environment Sciences, 2022)
Eutrophication of wetlands has been considered as a global level environmental problem due to wide range of environmental impacts caused by it. All the lake bodies are subjected to natural eutrophication process but anthropogenic activities like excessive utilization of inorganic fertilizers containing phosphorus and nitrogen in the farmlands which ultimately reach to water bodies through runoff during rainfall further maximizes the eutrophication. The research was conducted to find the trophic state of Lake Phewa, Lake Begnas and Lake Rupa which are three major lakes of Lake Clusters of Pokhara Valley, a Ramsar listed wetland from mid-hills of Nepal. Trophic state of lakes were classified on the basis of Carlson’s Trophic State Index. This index was calculated with the measurement of Secchi depth, Chlorophyll-a, and Total Phosphorus using standard methods. Study revealed that all three lakes were mesotrophic in both pre-monsoon and monsoon season. Lake Rupa had the highest Carlson Trophic State Index (CTSI) and Lake Begnas had lowest CTSI in both the season. Development of lake from oligotrophic to eutrophic state is a natural and gradual process and hence these lakes have increased chances of being eutrophic naturally along with natural process being crucially altered by cultural eutrophication which shortens the life expectancy of the affected aquatic body. Suitable conservation measures are needed to reduce organic load from lake to prevent from being further degraded.